2013
DOI: 10.1038/ng.2730
|View full text |Cite
|
Sign up to set email alerts
|

Variants in CPA1 are strongly associated with early onset chronic pancreatitis

Abstract: Chronic pancreatitis is an inflammatory disorder of the pancreas. We analyzed CPA1 encoding carboxypeptidase A1 in subjects with non-alcoholic chronic pancreatitis and controls in a German discovery cohort and three replication cohorts. Functionally impaired variants were present in 29/944 (3.1%) German patients and in 5/3,938 (0.1%) controls (odds ratio [OR] = 24.9; P = 1.5 × 10-16). The association was strongest in subjects aged ≤10 years (9.7%; OR = 84.0; P = 4.1 × 10-24). In the replication cohorts, defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
212
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 268 publications
(220 citation statements)
references
References 17 publications
2
212
0
6
Order By: Relevance
“…Mutations in the best characterized risk genes PRSS1 (cationic trypsinogen), SPINK1 (pancreatic secretory trypsin inhibitor), and CTRC (chymotrypsin C) stimulate activation of trypsinogen and result in elevated trypsin activity in the pancreas [4][5][6][7][8][9]. More recently, loss-of-function variants in the CPA1 gene encoding carboxypeptidase A1 were shown to increase risk for early onset CP [10]. The majority of impaired CPA1 variants exhibited a secretion defect due to intracellular misfolding and retention.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the best characterized risk genes PRSS1 (cationic trypsinogen), SPINK1 (pancreatic secretory trypsin inhibitor), and CTRC (chymotrypsin C) stimulate activation of trypsinogen and result in elevated trypsin activity in the pancreas [4][5][6][7][8][9]. More recently, loss-of-function variants in the CPA1 gene encoding carboxypeptidase A1 were shown to increase risk for early onset CP [10]. The majority of impaired CPA1 variants exhibited a secretion defect due to intracellular misfolding and retention.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological significance of complex formation has never been solved, although coordination of zymogen activation seemed a plausible possibility (14 -17). Our interest turned to these older studies when we identified that loss-of-function CPA1 mutations increased risk for chronic pancreatitis in children and we were searching for possible mechanisms to explain pathogenesis (6). We realized that complex formation among pancreatic protease zymogens has never been studied using post-genomic era tools.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid Construction and Mutagenesis-Construction of expression plasmids for human CELA3A, CELA3B, CTRC, CTRB1, CTRB2, CTRL1, CPA1, CPA2, and CPB1 in the pcDNA3.1(Ϫ) vector was described previously (2,6,8,9,49,50). C-terminal His 10 tags were engineered to the proelastase and chymotrypsinogen expression plasmids using gene synthesis (GenScript, Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations